THE POTENTIAL OF LIQUID ELECTROLYTE FROM Betta splendens WASTE FOR BATTERY APPLICATION - MOHD ZABIDI, MOHD ADLISYAM; NIK ALI, NIK AZIZ (Universiti Malaysia Terengganu Journal of Undergraduate Research, 2021)
This study focuses on the potential of liquid electrolyte from the wastewater of Betta splendens for battery application. In this analysis, two different parameters were manipulated, namely the time period and the electrical energy production from the different wastewater properties involving the use of Terminalia catappa leaves. The battery plays an important role in achieving universal access to clean, reliable, and affordable electricity services. The presence of ammonium (NH4+) in wastewater can produce renewable energy and help reduce environmental pollution. A voltage (V) unit is used in the measurement of energy potential by using a voltmeter. 25 B. splendens were cultured for five weeks in two aquariums, one without T. catappa leaves, and one with T. catappa leaves to get their weekly wastewater. Voltage output is measured against the number of weeks from the wastewater sample without T. catappa leaves and with T. catappa leaves. Observation shows that the highest voltage produced from the wastewater sample was from the first week for a motorcycle battery and the fifth week for the research battery. The results of the wastewater sample without T. catappa leaves and T. catappa leaves against the number of weeks on motorcycle battery is 4.210V and 5.129V respectively, while for the research battery is 0.5360V and 0.5380V respectively. The highest voltage values from a motorcycle battery and the research battery are taken to test their longevity for one month. The t-test analysis of this experiment shows an insignificant result for the motorcycle battery and a significant result for the research battery, thus proving that the concentration level of NH4+ has a significant effect on the amount of energy produced.